Epitope mapping of Brugia malayi ALT-2 and the development of a multi-epitope vaccine for lymphatic filariasis. Issue 1 (19th February 2016) - Madhumathi, J.; Prince, P.R.; Rao, D.N.; Karande, A.A.; Reddy, M.V.R.; Kaliraj, P.
Abstract: Human lymphatic filariasis is a neglected tropical disease, causing permanent and long-term disability with severe immunopathology. Abundant larval transcript (ALT) plays a crucial role in parasite establishment in the host, due to its multi-faceted ability in host immune regulation. Although ALT protein is a key filarial target, its exact function is yet to be explored. Here, we report epitope mapping and a structural model of Brugia malayi ALT-2, leading to development of a multi-epitope vaccine. Structural analysis revealed that ALT represents unique parasitic defence proteins belonging to a toxin family that carries a 'knottin' fold. ALT-2 has been a favourite vaccine antigen and was protective in filarial models. Due to the immunological significance of ALT-2, we mapped B-cell epitopes systematically and identified two epitope clusters, 1–30 and 89–128. To explore the prophylactic potential of epitope clusters, a recombinant multi-epitopic gene comprising the epitopic domains was engineered and the protective efficacy of recombinant ALT epitope protein (AEP) was tested in the permissive model, Mastomys coucha . AEP elicited potent antibody responses with predominant IgG1 isotype and conferred significantly high protection (74.59%) compared to ALT-2 (61.95%). This proved that these epitopic domains are responsible for the protective efficacy of ALT-2 and engineering protective epitopes as a multi-epitope protein may be a novel vaccine strategy for complex parasitic infections.